X‐ray tomographic observations of microcracking patterns in fibre‐reinforced mortar during tension stiffening tests. (13th April 2020) - Ducoulombier, Nicolas; Chateau, Camille; Bornert, Michel; Caron, Jean‐François; Aimedieu, Patrick; Weitkamp, Timm; Perrin, Jonathan; King, Andrew; Scheel, Mario
Abstract: For the last decades, new reparation or fabrication processes have been studied to replace traditional rebar by roving of different mineral or organic fibres to avoid corrosion issues. Such materials refer to the family of cementitious composite. Their tensile strength would directly depend on the proportion of reinforcement and strongly on the interfacial mechanical properties between fibres and cementitious matrix. From now, evaluation of interfacial properties was mostly limited to the use of force–displacement curves obtained from mechanical experiments. This work presents a new methodology using micromechanical tension stiffening tests combined with X‐ray computed tomography (XRCT) observations, performed at the Anatomix beamline at Synchrotron SOLEIL, and specific image processing procedures. Multi‐XRCT acquisitions with suitable scanning strategy are used to image the whole fibre‐matrix interface along centimetric samples at four to five different levels of loading magnitude. Intensive image processing is then performed on tomographic images including digital volume correlation (DVC), image subtraction and Hessian‐based filtering. This experiment allows to study damage mechanisms at small scale. The proposed methodology shows great potential to provide both qualitative and quantitative elements on interfacial mechanical behaviour such as crack growth and crack orientation. The interface between mortar and sufficiently small multi‐fibre yarn used in this paper is shown to behave in certain condition as traditional rebar interface producing conical cracks in the surrounding matrix rather than debonding in mode 2, permitting a much higher energy dissipation during debonding. According to this study, conical cracks repartition and geometry are mostly influenced by the cementitious matrix. The spacing between cracks goes from 50 to 100 μm, and the angle between crack normal vector and yarn orientation goes from 35° to 50°.